Na trilha do desenvolvimento profissional: percepções de professoras em formação continuada acerca do ensino de oralidade - Moraes, Laura Remus (Universidade do Vale do Rio dos Sinos, 2019)
Aiming to understand the Portuguese language teachers’ perceptions on the teaching of orality, this project proposes to investigate the oral production of a group of teachers that are taking part on a continued formation course. In which way such perceptions, emerged from the oral production and the conflict of representations, give us clues of the teaching’s self-consciousness and professional development is what we bring into the spotlight. This thesis is part of a greater project “Formação continuada e comunidades de desenvolvimento professional: aproximações teórico-práticas” (CNPq), coordinated by Dr. Professor Ana Maria de Mattos Guimarães and by Dr. Professor Anderson Carnin, from the Universidade do Vale do Rio dos Sinos (UNISINOS). The theorical cornerstone that supports this project is the Socialdiscursive Interactionism (BRONCKART, 1999, 2006a, 2006b, 2008, 2013) which attributes to the acting and to the language an essential part in human development. Taking the idea of work proposed by this theory’s guideline, we focus on the notion of represented work, from the data generated in a continued formation context, more specifically in a workshop dedicated to work and teaching of orality. For the analysis of this data we used the Bronckart’s textual architecture (1999). Others important concepts to this very same thesis are the notion of textual genres according to Bakhtin and Voloshinov BAKHTIN, 1997; VOLOSHINOV, 2006) and oral genres in education. The results achieved show the relevance of the conceptions’ analysis on the teaching of orality in a context of continued formation.
Keywords: Formação continuada; Ensino de língua portuguesa; Oralidade; Gêneros orais; Desenvolvimento profissional; Continuing education; Portuguese language teaching; Orality; Oral genres; Professional development; ACCNPQ::Lingüística, Letras e Artes::Lingüística